ANALISIS IMPLEMENTASI PENDIDIKAN KARAKTER DIMENSI KREATIF PADA TEMA GAYA HIDUP BERKELANJUTAN SISWA SEKOLAH DASAR - Fianita, Shera; Novi Irmaningrum, Rizka; Miftachul Huda, Mochammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the implementation of creative dimension character education on the theme of sustainable lifestyle for grade IV students of SDN 2 Pengangsalan. This study uses a descriptive qualitative approach. The subjects in this study are grade IV teachers and grade IV students of SDN 2 Pengangsalan. Using data collection techniques, namely observation, interviews, and documentation studies. The results of this study are that: 1) The character education of the creative dimension of the sustainable lifestyle theme of grade IV students of SDN 2 Pengangsalan is classified as less visible. This is reviewed based on the indicators of the creative dimension which include: students are less able to produce new ideas, students are less able to produce works, and students are less able to find alternative solutions or compare ideas with their peers 2) There are three supporting factors, namely students easily understand the material because it is directly related to daily life, teachers use learning media when explaining the material, and teachers design learning that involves dimensional characters creative in various subjects, for example in SBDP and IPAS subjects 3) There are three inhibiting factors, namely students have not been given material but first convey their inability to participate in learning, especially during project-based learning, students are less interested in learning, especially in P5 learning, so teachers need to motivate students, and students also have difficulty understanding the explanation of the material from the teacher, because students are not used to using Indonesian.